Theoretical studies on the absorption spectra of cis-[Ru(4, 4′-COO-2, 2′-bpy)2(X)2]4−, (X = NCS, Cl) and panchromatic trans-terpyridyl Ru complexes including strong spin–orbit coupling1. Issue 18 (14th May 2015) - Mishima, Kenji; Kinoshita, Takumi; Hayashi, Michitoshi; Jono, Ryota; Segawa, Hiroshi; Yamashita, Koichi; Lin, Sheng Hsien
<x xml:space="preserve">Abstract</x> TD-DFT formalism including spin–orbit coupling termed as first-order perturbation can reproduce the long-wavelength edge of the DX1 dye molecule.